"العلاقة بين إدارة تكلفة الجودة (COQ) والأداء الاقتصادي للمصارف" (Comprehensive Journal of Science, 2026)
This study aims to analyze and measure the relationship between Cost of Quality (COQ) management, with its four components—prevention costs, appraisal costs, internal failure costs, and external failure costs—and the economic performance of commercial banks operating within the jurisdiction of Al-Abyar Municipality, in light of the operational and competitive challenges facing the Libyan banking sector. The study adopted a descriptive–analytical approach and used a questionnaire as the main data collection tool, targeting a sample of 70 employees across different administrative levels, with data analyzed using advanced statistical techniques, including correlation coefficients and linear regression, through SPSS software. The findings revealed a strong and statistically significant relationship between Cost of Quality management and economic performance, showing that greater emphasis on prevention and appraisal costs improves operational efficiency and cost rationalization, while higher internal and external failure costs negatively affect economic performance; accordingly, the study recommends that commercial banks adopt an effective and integrated Cost of Quality management system as a strategic approach to enhancing economic performance and strengthening financial sustainability in the Libyan banking environment.